Exploitation of contract document for construction project planning and controlling - Ali, Aminudin (2006)
Construction industry was plague with multitude of criticism and tribulations in the perspective of the client for cost overruns and delays. The broad-spectrum regions of problems were within the planning and controlling functions. Proper contract documentation between contracting parties within the planning and controlling functions are able to reduce the predicament. A Document Study was done for 16 numbers of construction contract documentation projects in UTM during the period of the 7th Malaysians’ Plan from 1995 to 2000 with the total value of all projects in the excess RM70 million. The Client, Consultant, and Contractor become the main respondent target. The process of review, analyze and synthesis of contract document reveal 485 verses and phrase related to project planning and controlling functions that is further synthesis into 209 keywords. Time functions were establish to be the most important factor of planning and controlling within the contract document followed by cost function. The usage of contract document identifies construction activity function scored the highest within the content of Construction Drawing and secondly, the construction cost function within the content of Bills of Quantities. The respondent rated the highest score for the contract document to be very important for construction planning and controlling. In general, the contract document is also rated as highly used for construction planning and controlling function. Proposals were made to introduce new Bills of Activities in the contract document using a selected project for the exploitation validation. Microsoft Project 2003 was utilized to simulate the proposal. Finally, for the exploitation of the contract document, 93% of the respondent agreed that the contract document can be modified to become a Master Plan for the construction planning and control function to be contracted in the contract document, legally and binding